Fully Characterized Mature Human iPS- and NMP-Derived Motor Neurons Thrive Without Neuroprotection in the Spinal Contusion Cavity - Olmsted, Zachary T.; Stigliano, Cinzia; Marzullo, Brandon; Cibelli, Jose; Horner, Philip J.; Paluh, Janet L. (Frontiers in Cellular Neuroscience, 2022)
Neural cell interventions in spinal cord injury (SCI) have focused predominantly on transplanted multipotent neural stem/progenitor cells (NSPCs) for animal research and clinical use due to limited information on survival of spinal neurons. However, transplanted NSPC fate is unpredictable and largely governed by injury-derived matrix and cytokine factors that are often gliogenic and inflammatory. Here, using a rat cervical hemicontusion model, we evaluate the survival and integration of hiPSC-derived spinal motor neurons (SMNs) and oligodendrocyte progenitor cells (OPCs). SMNs and OPCs were differentiated in vitro through a neuromesodermal progenitor stage to mimic the natural origin of the spinal cord. We demonstrate robust survival and engraftment without additional injury site modifiers or neuroprotective biomaterials. Ex vivo differentiated neurons achieve cervical spinal cord matched transcriptomic and proteomic profiles, meeting functional electrophysiology parameters prior to transplantation. These data establish an approach for ex vivo developmentally accurate neuronal fate specification and subsequent transplantation for a more streamlined and predictable outcome in neural cell-based therapies of SCI.